“EXPRESSIVE GRAPHICS AS A COMPONENT OF THE LANGUAGE GAME IN LEWIS CARROLL’S LITERARY FAIRY TALE ALICE’S ADVENTURES IN WONDERLAND” BY OLHA KOZII - Saidova Kamola Olim qizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Annotation: Lewis Carroll’s Alice’s Adventures in Wonderland (1865) is widely recognized for its innovative use of language, nonsense, and playful narrative structures. While much research has focused on Carroll’s linguistic creativity, less attention has been paid to the interaction between text and illustrations. Kozii (2024) emphasizes that expressive graphics function as an integral part of Carroll’s literary language game, enriching the narrative and creating a multi-layered literary experience. This thesis explores how Carroll’s illustrations and textual play together contribute to the artistic and pedagogical value of his work for children.